What Drives High Growth? Characteristics of Australian Firms. Issue 318 (27th May 2021) - Majeed, Omer; Balaguer, Antonio; Hansell, David; Hendrickson, Luke; Latcham, Abasi; Satherley, Tessa
Abstract : Using firm‐level data, we analyse the patterns, innovation characteristics and determinants of turnover high‐growth firms (HGFs) in Australia. We find most HGFs do not stay in the high‐growth phase for long, and following the Global Financial Crisis the proportion of HGFs has declined. For HGFs, the results suggest that innovation in goods and services has a much greater impact on turnover growth than for the average firm. For all firms, innovations in goods and services and marketing, and business focus on innovation contribute to turnover growth. Finally, HGFs generate greater returns on investment in research and development than slower growing firms.